2017
DOI: 10.1002/jbmr.3290
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Serum IGF-1 Associated With Hepatic Osteodystrophy Is a Main Determinant of Low Cortical but Not Trabecular Bone Mass

Abstract: Hepatic osteodystrophy is multifactorial in its pathogenesis. Numerous studies have shown that impairments of the hepatic growth hormone/insulin-like growth factor-1 axis (GH/IGF-1) are common in patients with non-alcoholic fatty liver disease, chronic viral hepatitis, liver cirrhosis, and chronic cholestatic liver disease. Moreover, these conditions are also associated with low bone mineral density (BMD) and greater fracture risk, particularly in cortical bone sites. Hence, we addressed whether disruptions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 89 publications
(175 reference statements)
0
18
0
Order By: Relevance
“…Osteoporosis was associated with primary biliary cirrhosis (PBC) and was a risk factor for vertebral fracture (Guanabens et al 2010), further studies that the links of TAA, PBC, and vertebral fracture will be necessary to establish their role in the pathogenesis of liver injury. Then again, some studies suggested vitamin K2, Zinc and selenoprotein P have important effect on bone metabolism (Lwamoto et al 2011;Pietschmann et al 2014;Sun et al 2011), insulin-like growth factor-1 (IGF-1) is a main determinant of low cortical but not trabecular bone mass (Liu et al 2018). We guess IGF-1 associated with metabolic bone disease.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Osteoporosis was associated with primary biliary cirrhosis (PBC) and was a risk factor for vertebral fracture (Guanabens et al 2010), further studies that the links of TAA, PBC, and vertebral fracture will be necessary to establish their role in the pathogenesis of liver injury. Then again, some studies suggested vitamin K2, Zinc and selenoprotein P have important effect on bone metabolism (Lwamoto et al 2011;Pietschmann et al 2014;Sun et al 2011), insulin-like growth factor-1 (IGF-1) is a main determinant of low cortical but not trabecular bone mass (Liu et al 2018). We guess IGF-1 associated with metabolic bone disease.…”
Section: Discussionmentioning
confidence: 89%
“…Statistical signi cance differences between groups were assessed by one-way analysis of variance (Anova) followed by the Dunnett and LSD post hoc test for multiple comparisons. All data were analyzed using the SPSS statistical package version 22.0 for Windows (IBM, Armonk, NY, USA). P < 0.05 indicated a statistically signi cant difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers concluded that low bone mineral density is highly prevalent in this group of patients, and vitamin D levels and severity of liver disease are correlated with low BMD [ 4 ]. The pathogenic mechanism underlying this reduction is hypothesized in the literature to be a decrease in the proliferative capacity of osteoblasts with increasing bilirubin levels, which is dose dependent [ 4 , 5 , 24 , 25 ]. It is noteworthy that vitamin D3 is hydroxylated in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin-like growth factor-1 ( IGF-1 ), a polypeptide containing 70 amino acid residues, exists almost all tissues in mammals, and can accelerate cell proliferation and differentiation, functioning as a mitosis promoter for many types of cell (including osteoblasts). [10] IGF-1 pathway can regulate bone metabolism through diverse pathways. IGF-1 can facilitate the synthesis and mineralization of bone matrix through mitosis-independent pathway, and affect bone metabolism through regulating the functions of bone cells.…”
Section: Introductionmentioning
confidence: 99%